Application of MRI of the wrist for age determination in international U-17 soccer competitions - Dvorak, J.; George, J.; Junge, A.; Hodler, J. (BMJ Publishing Group, 2007)
In order to guarantee equal chances for different age groups, age-related tournaments for male and female players have been established in soccer. However, while registration at birth is not compulsory in some countries, other methods of age determination are needed to prevent participation in the incorrect age group